Flutter Analysis Of A Scaled Model Of An Eagle 150b/Ac Wing - Mohd. Rafie, Azmin Shakrine (2007)

(untitled)
An investigation of the problem of the flutter condition of an Eagle 150B aircraft wing is undertaken. The research is largely devoted to investigating the adequacy of the ideal flutter theory that has been employed to predict flutter boundary for such wing. A series of panel flutter experiment carried out in UPM 1m × 1m wind tunnel at Mach number up to 0.132 are described in detail. Furthermore, an extensive parametric computational analysis has been conducted to improve flutter condition by reconfiguring the wing design specification. For experimental analysis, the ground test which includes static and dynamic tests of the wind model has been performed followed by the wind tunnel testing. The data gathered from the wind tunnel testing is analyzed using the logarithmic decrement method so that the flutter speed can be predicted. The wing model mounting system test rig has been designed and developed together with the data acquisition system which is used for data collection. In order to validate the experimental technique, wind tunnel testing using three different types of materials for rectangular flat plate has been conducted. The types of materials used are aluminum 6061, mild steel and stainless steel. The agreement between experimental technique and computational analysis is acceptable since the error of difference is less than 6 percent. MSC. Patran and Nastran software have been used to predict the flutter condition since it has the capability to carry out the aeroelasticity analysis of the actual wing and wing model. The PK-method and aerodynamic doublet lattice methods were selected for this analysis as it provides the eigenvalue solutions in the form of the V-g and V-f graphs. Validation of the computational analysis with two existing published results is performed to ensure the results are reliable. The parametric study produced the results on the effects of the mass, altitude, span length, stiffness and center of gravity position against the flutter speed condition. This research work may conclude that both techniques are reliable to investigate flutter speed since the validation results showed a good agreement. It was also found that through extensive parametric study, several suggestions have been made to reconfigure the wing in order to improve the flutter condition.